Parasitoids of Heterogynis Rambur (Lepidoptera: Zygaenoidea, Heterogynidae) - Žikić, Vladimir; Stanković, Saša S.; Tschorsnig, Hans-Peter; León, Yeray Monasterio; De Freina, Josef J. (Archives of Biological Sciences, 2018)
Paper description: All presented host and parasitoid species are already known from the relevant literature, and most host-parasitoid associations. We present two new parasitoids Brachymeria inermis and Diplazon laetatorius associated with Heterogynis zikici. This work is a compilation of all available data and new findings in Europe for the species of the family Heterogynidae and their parasitoids. Abstract: Nine parasitoids of the moth genus Heterogynis are presented: six species of Hymenoptera from the families Chalcididae, Eulophidae and Ichneumonidae (Agrothereutes hospes (Tschek), Baryscapus endemus (Walker), Brachymeria inermis (Fonscolombe), Diplazon laetatorius (F.), Itoplectis maculator (F.) and Trichomalopsis heterogynidis Graham), and three Diptera, family Tachinidae (Compsilura concinnata (Meigen), Exorista segregata (Rondani) and Phryxe hirta (Bigot)). Two of these species, Trichomalopsis heterogynidis and Phryxe hirta, are oligophagous parasitoids specialized on the genus Heterogynis. We also identified two newly recorded parasitoids of Heterogynis: Brachymeria inermis (Chalcididae) and Diplazon laetatorius (Ichneumonidae). https://doi.org/10.2298/ABS180709039Z Received: July 9, 2018; Revised: August 28, 2018; Accepted: August 31, 2018; Published online: September 26, 2018 How to cite this article: Žikić V, Stanković SS, Tschorsnig H, León YM, de Freina JJ. Parasitoids of Heterogynis Rambur (Lepidoptera: Zygaenoidea, Heterogynidae). Arch Biol Sci. 2018;70(4):749-55.